1988
DOI: 10.1002/aic.690340213
|View full text |Cite
|
Sign up to set email alerts
|

A novel hollow‐fiber reactor with reversible immobilization of lactase

Abstract: Experimental and theoretical studies on a backflush hollow-fiber enzymatic reactor (HFER) were conducted in this work for a lactose/ lactase system. An A. niger lactase was chosen, from the four lactases tested, for reversible immobilization in the sponge layers of the fibers. An enzyme loading procedure was developed that allowed reliable and reproducible operation of the hollow-fiber reactor and produced industrially significant conversions without apparent change in the activity or stability of the lactase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…It was reported that the performance of the PFMR in a diffusion mode was the same as that of a typical plug‐flow reactor. However, the performance of the PFMR in a filtration mode was identical to that of the CSTMR 7, 8, 16. Furthermore, the performance of the CSTMR was found to deteriorate rapidly as a result of inactivation of enzymes by the shear stress or sedimentation on the membrane 14, 15…”
Section: Introductionmentioning
confidence: 93%
“…It was reported that the performance of the PFMR in a diffusion mode was the same as that of a typical plug‐flow reactor. However, the performance of the PFMR in a filtration mode was identical to that of the CSTMR 7, 8, 16. Furthermore, the performance of the CSTMR was found to deteriorate rapidly as a result of inactivation of enzymes by the shear stress or sedimentation on the membrane 14, 15…”
Section: Introductionmentioning
confidence: 93%
“…An enzyme solution is ultrafiltered from the spongy side (porous substructure) of an asymmetric ultrafiltration membrane to the skin side; this introduces the enzymes in the spongy matrix. Feed solution is also supplied from the same side; product solution goes out through the membrane skin (see Jones et al 73 for a brief introduction to the literature of hollow fiber enzymatic reactors employing this method of immobilization). An example of this type of immobilization in the context of aqueousorganic enzymatic processing has been illustrated in section 2.4.4.…”
Section: Segregation Of the Catalyst (And Cofactor) In Amentioning
confidence: 99%
“…When the PFMR is operated in a diffusion mode, its performance is that of a typical plug flow reactor (5). On the other hand, the performance of the PFMR operated in a filtration mode is that of a CSTMR (7). Furthermore, the performance of the CSTMR was found to deteriorate rapidly due to inactivation of the enzymes by the shear stress or sedimentation on the ultrafiltration membrane (8).…”
Section: Introductionmentioning
confidence: 99%